Implementasi Etika Bisnis Islam di Kalangan Pedagang Pada Pasar Tradisional Kota Serbelawan - Insyrah, Athala Rania; Afandi, Ahmad (-, 2023)
This study aims to determine the implementations of islamic business ethics among traders at the Traditional Market in Serbelawan city. This study uses a qualitative method with descriptive method. This research is a field study (field research ). Data source on this research includes primary data collected directly through phenomena in  the area research and secondary data collected indirectly through the literature which is relavant. Data collection techniques in this study include interviews, observation and documentation. Data analysis in this study was carried out through data reduction techiques, presentation of data and verification of data. The data validity technique triangulation. The results of this study indicate that traders in the city traditional market seberlawan applies the principles of islamic business ethics such as honesty, integrity, fairness and social responsibility. Implementation of islamic business ethic also provides long term benefits in relationships  with customers and society and get blessings. However barries include lack of understanding, intense competition, limited resources lack of legal oversight, and difficulties with halal certification. It takes effort to provide understanding, traning, and support from government and related institutions